Effects of beta-alanine combined with sodium bicarbonate on freestyle swimming performance - Coelho, D. F.; de Salles Painelli, V.; Campos, P. L.; Artioli, G. G.; de Jesus, F.; Galves, V. F.; de Oliveira, N.; do Carmo, C. A.; Solis, M. Y.; Benatti, F. B.; Roschel, H.; Sale, C.; et al. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Muscle acidosis is a major cause of fatigue during high-intensity exercise. Anaerobic contribution to simulated swimming bouts of 100 and 200 yd is known to be high. Few nutritional aids are able to reduce intramuscular H+ accumulation, namely sodium bicarbonate (SB) and beta-alanine (BA) supplementation. Two studies were conducted to investigate the effect of BA supplementation alone (study A) and the combined effect of BA plus SB on 100-m and 200-m swimming performance (study B). Methods: In Study A, 16 trained swimmers received either or BA (3.2 g/d for 1 week plus 6.4 g/d for 4 weeks) or placebo (PL). At baseline and after 5 weeks, the athletes completed simulated 100-m and 200-m freestyle swimming races. In Study B, 14 trained swimmers received either BA (3.2 g/d for 1 week plus 6.4 g/d for 3 weeks) or PL. Swimming time trials were performed at baseline, after 4 weeks and following 4 days of combined SB and PL supplementation, in a crossover fashion. Blood lactate was assessed in both studies. Results: Study A: BA supplementation significantly improved performance in the 200-m race by 2.0% (-2.8 seconds, p=0.01). Study B, both BA and SB alone improved 200-m time trial performance when compared to PL (BA-SB: 2.11%, PL-SB: 1.43%; BA-PL: 1.2%, p<0.05). The co-ingestion of BA plus SB provided no further benefit in comparison to BA or SB alone (p=0.78 and p=0.53, respectively). BA, with or without SB, had no significant effect on 100-m time trial performance. Blood lactate concentration increased, as a function of exercise trials. However, SB led to greater lactate accumulation when compared with other conditions. Discussion: BA supplementation effectively improved the 200-m freestyle swimming performance. Our additional results indicated that BA and SB were equally capable of improving swimmers performance; the co-ingestion of both supplements promoted a further non-significant improvement. SB resulted in higher blood lactate concentration after the exercise, probably caused by an SB-induced increased activity of monocarboxylate transporter-1 (Requena et al., 2005). Neither BA nor SB promoted a significant improvement in 100-m time-trial performance, which is in line with other studies (Webster et al., 1993; Derave et al., 2007).